The regulatory role of oxidative stress in the tooth movement process of rats with chronic fluorosis - Lingyan Lai; Wanxin Chen; Yue Hao; Bo Chen; Hua Yang (BMC Oral Health)
Abstract Background Clinically, fluorosis patients exhibit delayed orthodontic tooth movement and compromised retention. Experimental studies in fluorosis-exposed rats demonstrate suppressed tooth movement, impaired periodontal angiogenesis, and downregulated VEGF/PI3K/AKT/eNOS signaling. Oxidative stress is critical in periodontal remodeling during orthodontic treatment, yet its role in fluorosis-related movement alterations remains unclear. Methods Seventy 3-week-old Sprague-Dawley rats (body weight 60 ± 5 g) were randomly allocated into experimental groups. Ten rats served as a baseline group (0 day). The remaining 60 were randomized into three groups: control (C), orthodontic (O), and fluorosis orthodontic (FO), (n = 20 rats), subdivided into 3, 7, 14, and 21 days subgroups. C, O groups and blank baseline subgroup received purified water (fluoride < 0.08 mg/L, below the national standard of 1 mg/L), the FO group and fluorosis baseline subgroup drank 150 mg/L NaF water to establish a fluorosis model. After 3 months, orthodontic appliances were applied to O and FO groups. Fluoride accumulation (blood/urine), tooth movement rate and oxidative stress markers (SOD, CAT, MDA, and 8-OHdG) were analyzed. Results 1 FO group showed elevated blood/urine fluoride levels with C group (P < 0.05). Successful tooth movement was confirmed by interdental expansion.2 FO group exhibited slower tooth movement rate than O group (P < 0.05)0.3 Oxidative stress dynamics: Intergroup Difference: SOD and CAT levels were lowest in the FO group before 7 days, while MDA and 8-OHdG levels were highest in the FO group (P < 0.05), with differences narrowing in later stages.Intragroup Comparisons: SOD: C group: Levels initially increased, peaked at 14 days, and subsequently declined.O group: Levels consistently decreased over time.FO group: Levels exhibited a continuous upward trend.CAT: C group: Levels fluctuated in the early phase and sharply increased in the later phase.O group: Levels initially rose and then declined.FO group: Levels persistently increased throughout the study.MDA: C and FO groups: Levels continuously decreased.O group: Levels first increased, then decreased with fluctuations.8-OHdG: C group: Levels initially rose and later declined.O group: Levels fluctuated markedly.FO group: Levels first decreased and then slightly rebounded. Conclusion Fluorosis inhibits early-stage tooth movement (3–7 days) through aggravated oxidative stress, with diminishing effects over time as compensatory antioxidant mechanisms emerge.